Site-specific characterization of envelope protein N-glycosylation on Sanofi Pasteur's tetravalent CYD dengue vaccine. Issue 11 (10th March 2015) - Dubayle, Jean; Vialle, Sandrine; Schneider, Diane; Pontvianne, Jérémy; Mantel, Nathalie; Adam, Olivier; Guy, Bruno; Talaga, Philippe
Highlights First report assessing the site-specific N-glycosylation of the E-protein from CYD. Both Asn67 and Asn153 sites are glycosylated. The most abundant glycoforms at each site of the E-protein are different. The main glycoform detected at Asn67 is able to interact with DC-SIGN co-receptor.